Transparência e privacidade no âmbito das estatais mineiras: análise da implementação da Lei de Acesso à Informação e da Lei Geral de Proteção de Dados e sua relação com os princípios da governança pública - Lima Júnior, Fernando Nogueira (2023)
The research seeks to analyze the implementation of the Law of Access to Information (LAI) and the General Law of Data Protection (LGPD), in the scope of the state companies of Minas Gerais, and its relationship with the principles of public governance. The study was based on bibliographic, documentary and field research, the latter carried out in two phases, the first of a quantitative approach, developed through the application of two structured questionnaires, and the second of a qualitative approach, carried out through semistructured interviews. The object of analysis are the 12 (twelve) state-owned companies controlled directly by the Minas Gerais State Government. After carrying out the stages of the research, a comparative examination was carried out between the results obtained in the documentary analysis, in the questionnaires and in the interviews. The results of the desk research reveal that, although it may seem contradictory to protect personal data and determine access to public information, the LAI and LGPD are not at different poles. The provisions that protect privacy can coexist with the principles of governance and transparency, and there are no aspects of incompatibility or inconsistencies. The field research indicated that state-owned companies in Minas Gerais have satisfactorily met the stages for implementation and execution of the LAI and LGPD, although some have shown difficulties in making the duty of transparency compatible with the protection of privacy. By establishing programs based on corporate governance principles, state-owned companies find it easier to systematically interpret the LAI and LGPD, creating appropriate information flows and a logical interpretative basis, which facilitates the dialogue between the right to the protection of personal data and access to public information, fostering transparency and privacy, essential features for the development of a governance regime that meets social concerns and the goals for which the state-owned companies were created.